Clinical Risk Factors affecting the Pregnancy Outcome using Pakistan Maternal Mortality Survey (PMMS) 2019 - Sehar Saleem, Sana Nazir, Seyab Yasin, Asifa Kamal, Maria Aslam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: South Asia is the world's most populous region, and it also has the highest rate of pregnancy loss. It is necessary to understand the risk factors for pregnancy loss in South Asian countries like Pakistan for reducing the global burden of pregnancy loss. Aim: To determine the potential clinical factors affecting pregnancy outcomes of Pakistani women aged 15-49 years during 2016-2019. Study design: This study was conducted using Pakistan Maternal Mortality Survey (PMMS 2019) during 2020-2021. All eligible ever-married women (n=7096) aged 15-49 were selected for this study. In this study, the clinical risk factors considered are fever, unconsciousness, high blood pressure, diabetes, vaginal bleeding, problems associated with the placenta, problems associated with the position of the baby, and preeclampsia. The response variable was pregnancy outcome comprising four categories that are live-birth, stillbirth, miscarriage, and abortion. A multinomial logistic regression model was applied to test the relationship between the dependent variable and each of the eight risk factors. Results: Multinomial logistic regression model identified that fever (OR=0.723), vaginal bleeding(OR=1.614), high blood pressure (OR=1.473), and problems associated with the position of the baby (OR=0.396)are significantly associated with a stillbirth at a 10% level of significance. Additionally, unconsciousness (OR=1.019) appears as a potential risk factor for abortion. Practical implication: Understanding the most significant risk factors that contribute to negative pregnancy outcomes, it can prioritize resources to improve maternal health. Also, assistance to healthcare providers and policymakers in making informed decisions regarding maternal health in Pakistan can be provided. Conclusion: Fever, vaginal bleeding, high blood pressure, problems associated with the position of the baby are significant risk factors of stillbirth. However, unconsciousness identified a risk factor of abortion. It is concluded that in Pakistan pregnancy loss can be reduced by controlling the prevalence of diseases during pregnancy. Keywords: Abortion, Clinical risk factors, Miscarriage, Multinomial logistic model, Pregnancy loss, Stillbirth